2020
DOI: 10.1108/srj-12-2019-0403
|View full text |Cite
|
Sign up to set email alerts
|

Linking green HRM practices to environmental performance through pro-environment behaviour in the information technology sector

Abstract: Purpose Existing literature acknowledges the role of green human resource management (GHRM) in shaping employees’ pro-environmental behaviour and environmental performance. However, limited studies have investigated the specific impacts of GHRM practices on pro-environmental behaviour from the employees’ perspectives. This study aims to conceptualise GHRM practices as internal resources that can be used to stimulate employee pro-environmental information technology (IT) behaviour. Design/methodology/approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
85
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(99 citation statements)
references
References 67 publications
12
85
2
Order By: Relevance
“…Past studies showed that OCBE-O result in upliftingthe Environmental Performance (Elshaer et al, 2020; Wiradirja et al, 2020).The results of hypotheses (H6, H7, H9) are according to the prior literature regarding mediating role of OCBE-O between green initiatives and Environmental Performance(Ogalo et al, 2020;Silvester et al, 2019;Yusoff et al, 2018). Recent studies represented that OCBE-O plays partial or complete mediation between GHRM practices (GPR, GRW, GTR) and Environmental Performance(Masri & Jaaron, 2017;Ojo et al, 2020). The notsupported mediation effect (H8) can be explained as Green Recruitment is failed to be related with OCBE-O significantly.…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…Past studies showed that OCBE-O result in upliftingthe Environmental Performance (Elshaer et al, 2020; Wiradirja et al, 2020).The results of hypotheses (H6, H7, H9) are according to the prior literature regarding mediating role of OCBE-O between green initiatives and Environmental Performance(Ogalo et al, 2020;Silvester et al, 2019;Yusoff et al, 2018). Recent studies represented that OCBE-O plays partial or complete mediation between GHRM practices (GPR, GRW, GTR) and Environmental Performance(Masri & Jaaron, 2017;Ojo et al, 2020). The notsupported mediation effect (H8) can be explained as Green Recruitment is failed to be related with OCBE-O significantly.…”
mentioning
confidence: 68%
“…GHRM uses HRM practices topositively impactthe environment (Ojo et al, 2020). GHRM activities help in enhancing positive outcomes relating to the environment (Pechancova et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous research has highlighted that organizational culture and environmental management are closely related [30,31]. An organization can improve its environmental performance by creating a culture that supports environmental management [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…The use of organization-wide measures for measuring resource consumption and waste is essential for long-term environmental performance. A conceptual model for sustainable development, which tracks and audits the production and use of assets, is also required for high achievement ( Ojo et al, 2020 ; Prakash and Das, 2022 ). Another important factor included in green HRM practices is green performance and appraisal.…”
Section: Literature Reviewmentioning
confidence: 99%